2022
DOI: 10.17762/ijritcc.v10i9.5714
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Classification of Sentiments from Restaurant Reviews Using Novel Fuzzy-Encoded LSTM

Abstract: User reviews on social media have sparked a surge in interest in the application of sentiment analysis to provide feedback to the government, public and commercial sectors. Sentiment analysis, spam identification, sarcasm detection and news classification are just few of the uses of text mining. For many firms, classifying reviews based on user feelings is a significant and collaborative effort. In recent years, machine learning models and handcrafted features have been used to study text classification, howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Dataset size [23], [25], [29], [31], [44], [45] <5,000 [20], [22], [26], [30], [43], [46] 5,000-20,000 [24], [36], [38], [47] 20,000-50,000 [21] 50,000-100,000 [33], [34], [35], [40] >100,000 [27], [28], [32], [37], [39], [41], [42] Not available…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Dataset size [23], [25], [29], [31], [44], [45] <5,000 [20], [22], [26], [30], [43], [46] 5,000-20,000 [24], [36], [38], [47] 20,000-50,000 [21] 50,000-100,000 [33], [34], [35], [40] >100,000 [27], [28], [32], [37], [39], [41], [42] Not available…”
Section: Literaturementioning
confidence: 99%
“…Performance metric [21], [25], [41], [47] Accuracy [28], [32] Accuracy, precision, recall [30], [44] Accuracy, F1-score [20], [23], [24], [26], [29], [31], [36], [37] Accuracy, precision, recall, F1-score [22], [27] Precision, recall, F1-score [38] F1-score [34] Perception score [46] Mapping quality characteristic [40] Relationship (online reviews-hotel sales) [43] Classify user component [33] Confusion matrix Consequently, it is deemed proficient at classifying forthcoming values. According to the data presented in Table 8, it can be observed that the random forest technique exhibits the highest level of accuracy among the ML algorithms, achieving a remarkable accuracy rate of 99.2% when applied to the TripAdvisor dataset.…”
Section: Literaturementioning
confidence: 99%
“…Londhe et al [10] propose a system that combines Long Short-Term Memory (LSTM), fuzzy logic, and incremental learning for sentiment analysis in restaurant reviews. The system effectively handles multi-category classification and captures cross-category correlations by incorporating binary classifiers and an ensemble approach.…”
Section: Sentiment Analysismentioning
confidence: 99%
“…Sentiment analysis [1,2], crucial for understanding public opinions on products and events, has become vital with the internet's growth, but analyzing vast online data poses challenges. The goal [3][4][5][6][7][8][9][10][11] is to assess sentiment, often on a positive-negative spectrum for written reviews. Sentiment analysis, situated at the intersections of computational linguistics, NLP, and data mining, utilizes techniques from these fields to extract sentiments from text.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the selection of domain-specific models features Convolutional Neural Network (CNN), Long Short-Term Memory (LSTM), and CNN-LSTM. The LSTM has been employed by(Londhe & Rao, 2022) to overcome the issues of short text classification in the restaurant sentiment analysis on Yelp dataset and(Khruahong et al, 2022) to analyze the relationship between social media use and its effect on community-based tourism in Thailand. On the other hand, CNN was used by(Mamatha et al, 2022) to deal with problem of review images sentiment classification for restaurants.…”
mentioning
confidence: 99%